Protective effect of bixin on cisplatin-induced genotoxicity in PC12 cells - dos Santos, Graciela Cristina [UNESP]; Mendonca, Leonardo Meneghin; Antonucci, Gilmara Ausech; dos Santos, Antonio Cardozo; Greggi Antunes, Lusania Maria; Pires Bianchi, Maria de Lourdes (Pergamon-Elsevier B.V. Ltd, 2012)
Bixin is the main carotenoid found in annatto seeds (Bixa orellana L.) and is responsible for their reddish-orange color. The antioxidant properties of this compound are associated with its ability to scavenge free radicals, which may reduce damage and protect tissues against toxicity caused by anticancer drugs such as cisplatin. In this study, the genotoxicity and antigenotoxicity of bixin on cisplatin-induced toxicity in PC12 cells was assessed. Cytotoxicity was evaluated using the mu assay, mutagenicity, genotoxicity, and protective effect of bixin were evaluated using the micronucleus test and comet assay. PC12 cells were treated with bixin (0.05, 0.08, and 0.10 mu g/mL), cisplatin (0.1 mu g/mL) or a combination of both bixin and cisplatin. Bixin was neither cytotoxic nor genotoxic compared to the controls. In the combined treatment bixin significantly reduced the percentage of DNA in tail and the frequency of micronuclei induced by cisplatin. This result suggests that bixin can function as a protective agent, reducing cisplatin-induced DNA damage in PC12 cells, and it is possible that this protection could also extend to neuronal cells. Further studies are being conducted to better understand the mechanisms involved in the activity of this protective agent prior to using it therapeutically. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cisplatin; Carotenoids; Protective effect; Pigments; Genotoxicity; Cell line